GE_GERICHTE C/17403/2013 vom 1. November 2013 - GE Cour de justice (2013)
; CONVENTION SUR LES ASPECTS CIVILS DE L'ENLÈVEMENT INTERNATIONAL D'ENFANTS | CLAH80.13.1.B:LF-EEA.5.A:LF-EEA.5.B:CCFR.372.:CCFR.373